A novel methodology for secured c-governance using Hadamard coding. (1st January 2012) - Mukherjee, K.; Sahoo, G.
Cloud computing has opened a viable business option for corporations, industry and government organisations. This new paradigm is capable to trim down cost, can endow organisations with usage-based pricing, enhance functionality, improved collaboration, communication, omnipresent of application and data. Keeping this in view, this new technology is a natural choice for government sectors as e-governance to hike the recital of government machinery. So, we propose here a cloud computing-based e-governance, i.e., c-governance. But this cutting age of technology is still in its infant stage. So cloud computing and c-governance has to address lot of key issues like – security, performance, availability, scalable software architecture, etc. On this context, this manuscript has focused on a new security framework, security algorithms for c-governance based on Hadamard matrix. The results of the implementations are presented in order to lay bare the effectiveness of the proposed framework and algorithms.